Risk analysis of terrorist attacks on LNG storage tanks at ports. (May 2021) - Zhu, Rongchen; Hu, Xiaofeng; Bai, Yiping; Li, Xin
Highlights: A risk analysis method of terrorist attacks on port's LNG Storage tanks is presented. This article conducted the risk analysis from multiple dimensions. Different scenarios are used to analyze potential consequences. Abstract: In recent years, with the increasing demand for liquefied natural gas (LNG) worldwide, a large amount of LNG is stored, processed, and transported in ports. The port's LNG storage tanks may become a hot target for terrorist attacks because the failure or destruction of these facilities will put markets, cities, and the environment at high risk. This article presents a new risk analysis method of terrorist attacks on the port's LNG Storage tanks. The steps are as follows: (1) Identify risk factors from a multidimensional perspective. (2) Analyze the risk using the Bayesian network and event tree. (3) Evaluate and quantify the accident consequence. (4) Use knowledge graph to store risk knowledge. We verify the effectiveness of the method through case studies. The defence capabilities of the police and different prevention strategies were studied. The results show significant differences in accident consequence between different defensive and emergency response forces. We also conducted nine scenario analysis, which could provide a theoretical basis and method support for public security and urban risk management departments' security prevention decisions.